Question
Find \( (a \circ b)(-2) \) \( \begin{array}{c}a(x)=x+1 \\ b(x)=3 x \\ (a \circ b)(-2)=\square \\ \text { Save answer }\end{array} \)
Ask by Munoz Knight. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( (a \circ b)(-2) = -5 \)
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Bonus Knowledge
To find \( (a \circ b)(-2) \), we first need to evaluate \( b(-2) \) using the function \( b(x) = 3x \). Calculating \( b(-2) \): \[ b(-2) = 3(-2) = -6 \] Next, we use the result from \( b(-2) \) to evaluate \( a(b(-2)) = a(-6) \) using the function \( a(x) = x + 1 \). Calculating \( a(-6) \): \[ a(-6) = -6 + 1 = -5 \] So, \( (a \circ b)(-2) = -5 \).